Proceedings of the 13th International Conference on Availability, Reliability and Security 2018
DOI: 10.1145/3230833.3230842
|View full text |Cite
|
Sign up to set email alerts
|

Let's shock our IoT's heart

Abstract: A fault attack is a well-known technique where the behaviour of a chip is voluntarily disturbed by hardware means in order to undermine the security of the information handled by the target. In this paper, we explore how Electromagnetic fault injection (EMFI) can be used to create vulnerabilities in sound software, targeting a Cortex-M3 microcontroller. Several use-cases are shown experimentally: control flow hijacking, buffer overflow (even with the presence of a canary), covert backdoor insertion and Return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…While these papers report single fault effects, recent works show that one fault injection or complex fault injection means can lead to the corruption of several consecutive instructions. Electromagnetic pulses can lead to the replay or the skip of several consecutive instructions, from two up to a dozen [20,5,19,15]. Laser-based fault injection techniques can also lead to the skip of few chosen instructions [8] or of a variable number of consecutive instructions, from 1 to 300 depending on the laser pulse duration [11].…”
Section: Threat Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…While these papers report single fault effects, recent works show that one fault injection or complex fault injection means can lead to the corruption of several consecutive instructions. Electromagnetic pulses can lead to the replay or the skip of several consecutive instructions, from two up to a dozen [20,5,19,15]. Laser-based fault injection techniques can also lead to the skip of few chosen instructions [8] or of a variable number of consecutive instructions, from 1 to 300 depending on the laser pulse duration [11].…”
Section: Threat Modelmentioning
confidence: 99%
“…Recent works have shown that it is possible to inject multiple faults [7] (i.e. at different instants) and to corrupt several consecutive instructions [20,5,11,15,8,6]. Faults can have a width varying from a few up to more than one hundred consecutively executed instructions.…”
Section: Introductionmentioning
confidence: 99%
“…As such, only a handful of the observed faults can be tracked down and explained by a modification of the bits in the instruction [31]. Last, but not least, electromagnetic fault injection usually exhibits poor repeatability [13], as low as a few percents in some cases. Conversely, another actively studied technique is laser fault injection, which offers several advantages when it comes to interpreting the observed faults.…”
Section: Related Workmentioning
confidence: 99%